From Accreditation Audit to Actionable Strategy: A Mixed-Methods, Priority-Setting Evaluation of Hospital Pharmacy Services under the 2024 Indonesian Hospital Accreditation Standards - Mohammad Febry Andintias; Hardiyani Presticasari (HM Publisher, 2026)
Hospital accreditation frameworks generate aggregate compliance scores that obscure the indicator-level heterogeneity on which meaningful quality improvement depends. The 2024 Indonesian Hospital Accreditation Standards (Standar Akreditasi Rumah Sakit/STARKES 2024) operationalise hospital pharmacy quality through seven Pharmaceutical Care and Drug Management (PKPO) standards, but no peer-reviewed study has yet linked STARKES 2024 compliance scoring to systematic priority-setting or to an implementation-ready action plan. In this descriptive evaluative, sequential explanatory mixed-methods study conducted at the Pharmacy Department of a Class C public hospital in Central Java, Indonesia, eight resident pharmacists (n = 8; institutional census) scored 53 STARKES 2024 indicators, triangulated through in-depth interviews, observation, patient-journey simulation, and document tracing. The Hanlon prioritisation method ranked residual gaps, and a facilitated focus-group discussion produced a SMART action plan. Aggregate compliance was 90.54% (95% CI 85.1–94.3; p < 0.001 versus the 80% threshold), with standard-level scores spanning 83.33–95.00% and a median absolute deviation of 4.72 percentage points. Hanlon analysis yielded three actionable top-tier priorities — collaborative therapeutic drug monitoring (OPR = 84.00), annual formulary evaluation (OPR = 74.67), and cytostatic compounding competency (OPR = 69.33) — robust across sensitivity perturbations. Pareto analysis concentrated 70.2% of the priority-weighted residual burden in the top three gaps. The study establishes the STARKES 2024 + Hanlon pairing as a discriminating, transferable template for translating accreditation compliance into measurable pharmacy quality improvement.